2019
DOI: 10.3390/ijerph16060961
|View full text |Cite
|
Sign up to set email alerts
|

Significant Impacts of Work-Related Cerebrovascular and Cardiovascular Diseases among Young Workers: A Nationwide Analysis

Abstract: Background: While occupational factors linked to the onset of cerebrovascular and cardiovascular diseases (CVDs) have been reported among workers, much remains unknown about the impacts that occupation has on the onset of CVDs in various age groups. We attempted to describe temporal trends in total and work-related CVDs (WRCVDs) rates stratified by age and year and explore the relative contributions of work to the CVD risk. Methods: This study was conducted using two populations from the Labor Insurance Databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Our study aligns with the findings of Hu et al [16], which indicated geographic differences in the downward trend of CVD death rates during that period. Evidence also suggests that the period and age trends of CVD rates differ between the working population and the overall Taiwanese population, with more severe relative effects observed in younger workers, particularly those aged < 55 years [17]. Compared to China, there has been a rapid increase in the ASIR of first-ever stroke in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Our study aligns with the findings of Hu et al [16], which indicated geographic differences in the downward trend of CVD death rates during that period. Evidence also suggests that the period and age trends of CVD rates differ between the working population and the overall Taiwanese population, with more severe relative effects observed in younger workers, particularly those aged < 55 years [17]. Compared to China, there has been a rapid increase in the ASIR of first-ever stroke in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases occur when coronary arteries are choked by plaques or atheroma in a process known as atherosclerosis (1) and work-related cardiovascular disorders (WRCVDs) are conditions of the heart or blood vessels that are caused by working conditions making them a work-related illness (2). Most of these conditions are associated with mental stress at work, low social support at work, exposure to ionizing radiation, noise and presence of physical hazard (3).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, 25% of the working population cannot work because of CVD. [6] Moreover, CVD affects the working-age population in lowand middle-income countries. For example, in sub-Saharan Africa, half of the cardiovascular deaths occur in the 30 to 69-year-old age group.…”
Section: Introductionmentioning
confidence: 99%